2014
DOI: 10.1002/0471250953.bi0210s48
|View full text |Cite
|
Sign up to set email alerts
|

Using the Structure‐Function Linkage Database to Characterize Functional Domains in Enzymes

Abstract: The Structure‐Function Linkage Database (SFLD; http://sfld.rbvi.ucsf.edu/) is a Web‐accessible database designed to link enzyme sequence, structure, and functional information. This unit describes the protocols by which a user may query the database to predict the function of uncharacterized enzymes and to correct misannotated functional assignments. The information in this unit is especially useful in helping a user discriminate functional capabilities of a sequence that is only distantly related to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…32−37 The identity of pyruvate as the source of the carbons in the imidazoline ring was established using 13 C pyruvate isotopologues in vitro, which showed that C2 and C3 of pyruvate are incorporated into the tRNA base and C1 is lost as an unidentified side product, proposed to be either carbon dioxide or formate. 33 TYW1, like other enzymes in the 100,000-plus membered radical SAM superfamily, 38 uses a SAM-bound [4Fe−4S] cluster to reductively cleave SAM, forming methionine and a highly reactive 5′-deoxyadenosyl radical species (dAdo•) that initiates radical-based chemistry. 39 TYW1 also has an auxiliary iron−sulfur cluster, identified as a [4Fe−4S] cluster by an electron paramagnetic resonance (EPR) and Mossbauer study.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32−37 The identity of pyruvate as the source of the carbons in the imidazoline ring was established using 13 C pyruvate isotopologues in vitro, which showed that C2 and C3 of pyruvate are incorporated into the tRNA base and C1 is lost as an unidentified side product, proposed to be either carbon dioxide or formate. 33 TYW1, like other enzymes in the 100,000-plus membered radical SAM superfamily, 38 uses a SAM-bound [4Fe−4S] cluster to reductively cleave SAM, forming methionine and a highly reactive 5′-deoxyadenosyl radical species (dAdo•) that initiates radical-based chemistry. 39 TYW1 also has an auxiliary iron−sulfur cluster, identified as a [4Fe−4S] cluster by an electron paramagnetic resonance (EPR) and Mossbauer study.…”
Section: ■ Introductionmentioning
confidence: 99%
“…TYW1, like other enzymes in the 100,000-plus membered radical SAM superfamily, uses a SAM-bound [4Fe–4S] cluster to reductively cleave SAM, forming methionine and a highly reactive 5′-deoxyadenosyl radical species (dAdo•) that initiates radical-based chemistry . TYW1 also has an auxiliary iron–sulfur cluster, identified as a [4Fe–4S] cluster by an electron paramagnetic resonance (EPR) and Mössbauer study .…”
Section: Introductionmentioning
confidence: 99%
“…The RS superfamily contains >100,000 members catalyzing a myriad of biologically important transformations. 13 The enzymes within this superfamily generally contain the CxxxCxxC motif, identified as the radical SAM signature sequence. 14 These conserved cysteines provide thiolate ligands to coordinate three iron atoms of a [4Fe-4S] cluster (referred to as the RS cluster) with the fourth iron of the cluster coordinated by the α-carboxylate and α-amino moieties of SAM (Fig.…”
mentioning
confidence: 99%
“…The S- adenosyl- l -methionine (AdoMet) radical enzyme superfamily has >300000 distinct members that carry out a plethora of diverse chemical transformations. 1 Most of the enzymes in this superfamily possess a characteristic CxxxCxxC motif housing a site-differentiated [4Fe-4S] cluster [reaction cluster (RC)] that in turn binds AdoMet at a unique iron. In the +1 oxidation state, the RC reductively cleaves AdoMet to form the 5′-deoxyadeonsyl radical intermediate (5′-dA • ).…”
mentioning
confidence: 99%